It’s fake, but i buy it! A study on the consumption of pirated and counterfeit products in the brazilian border cities of Santana do Livramento/BR and Rivera/UY - Silva, Andressa Hennig; Braz, Fernando Araújo; Floriano, Mikaela Prestes (Revista de Administração da UFSM, 2021)
Purpose – This study seeks to identify the behavior of buying pirated and counterfeit products in the border towns of Santana do Livramento/RS and Rivera/UY. Design/methodology/approach – In order to achieve the proposed objective, a quantitative, descriptive research was undertaken using the survey method. The study sample comprised 562 observations, 274 of respondents from the city of Santana do Livramento/RS and 288 from residents of the city of Rivera/UY. Findings – The main results show that there are not many differences in the opinions of buyers and Uruguayan respondents in relation to the consumption of pirated and counterfeit products, and issues related to price and belonging to a social group do not seem to be the main motivations for the family of types of products. Research limitations/implications – The study was limited with regard to the sample, which did not have a probabilistic nature. Thus, it is suggested that new studies that seek to represent the population, and that are carried out in other borders of countries, in order to understand the way in which cultures can interact and spread habits among them. Practical implications – As practical implications, the need to develop marketing objectives with the intention of minimizing the interest and purchase of counterfeit and pirated products is highlighted. Social implications – Regarding the social implications, the potential effects of the purchase and consumption of counterfeit products for individuals are highlighted, since such behavior can reflect negative aspects both for the physical health of consumers and for the economy of the losing country. millions in taxes. Originality/value – The originality of the study lies in the fact that it strengthens the findings on the subject in academics, in addition to bringing a comparison of consumer professionals of two nationalities.